The Role of User Value Co-Creation Behavior on Service Delivery Performance of Union Digital Center in Bangladesh - Zijun Mao; Bikram Biswas; Mohammad Nur Ullah; Md Mostafizur Rahman; Farhana Rahman (SAGE Open)
Drawing on Stimulus-Organism-Response (SOR) and Attitude-Behavior-Context (ABC) models, this study aims to propose a comprehensive theoretical framework, measuring the service delivery performance of Union Digital Center (UDC) on citizen satisfaction and use behavior by utilizing the extension of the SERVQUAL model with another two dimensions: “Information Quality” and “Service Availability.”“Value co-creation” is also used as a boundary condition in this integrated framework. This study is the first endeavor of the SERVQUAL model to explore the satisfaction of UDC users in Bangladesh with the role of user co-creation behavior. In doing so, a total of 411 data was collected from the users of UDC through a structured questionnaire. This study then utilized PLS-SEM, Mplus and PROCESS-Macro for hypothesis testing and other inferential statistics and found a significant impact of the exogenous variables (service availability, information quality, responsiveness, reliability, assurance, information quality empathy, and tangible) on satisfaction and use behavior. A moderated role of value co-creation was found in relationship between all the dimensions of service quality except information quality, assurance, and empathy. Thus, promoting value co-creation, meaning involving citizens in the service delivery process, would be a good strategy that may influence their attitude and further use. The findings of this study can be used as a theoretical basis, especially for improving the service quality and accelerating user satisfaction of digital centers in rural areas. Furthermore, this integrated framework can be applied to evaluate the digital service centers in other developing countries.